Overview of the Efficient Tehnologies for Power Generation Based on Coal - Enver Agić*; Damir Šljivac; Branka Nakomčić-Smaragdakis (Tehnički Vjesnik, 2021)
This paper gives an overview of effective technologies for coal-based electricity generation. The introductory chapter presents the development of efficient electricity production from the end of the nineteenth century to the present, and the emphasis is placed on the examination of modern efficient technologies for electricity production in the 21th century with a detailed comparison of hard coal combustion (PCC) and fluidised bed combustion (CFCB) technologies. Pollutants such as carbon monoxide (CO), sulfur oxides (SOx) and nitrogen oxides (NOx) occur during the process of coal combustion. SO2 and NOx cause the acid rain and CO2 gas is the most responsible for the greenhouse effect. With using the new fire-resistant steels based on nickel, the TPP with advanced ultra-supercritical steam parameters (A-USC) with t = 700 °C and working p = 350 bar are expected, and also, this will increase the efficiency above 50%. In this paper, this and other emerging technologies have been presented as well as the comparison of their characteristics.